Kooperationen der Teaching Library an der Universitätsbibliothek Wien - Rohrmoser, Manuela; Schachl, Irene (GMS Medizin – Bibliothek – Information, 2014)
[english] The cooperation of university libraries with intra- and extra-university institutions with the goal of teaching information literacy has increased significantly in recent years. The topic of information literacy and the accurate handling of information have become a key skill in many areas, in society, in the economy, in education as well as in further training. Therefore, libraries are increasingly becoming educational institutions within the universities, colleges, schools and other institutions to which they belong.Vienna university library participates in this development and offers assistance for the accurate handling of information as the basis of writing academic or pre-academic papers in a variety of collaborations. These include courses at university as well as school levels which are tailored to the target groups. Some of these collaborations are discussed in detail: the training of PhD students and writing mentors in individual study courses, the support for pre-scientific work in schools and the training of school librarians.